TANGGUNG JAWAB KEWAJIBAN HUKUM PERUSAHAAN UNTUK PERUBAHAN IKLIM BERDASARKAN PERJANJIAN INTERNASIONAL DAN REGULASI NASIONAL - Lumban Gaol, Chandra Erick Manaek Pandapotan; Elisatris Gultom (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Global climate change has become a central issue in international and national legal discourse. The coal mining industry, particularly PT Bukit Asam Tbk (PTBA), plays a crucial role in climate change mitigation and adaptation. The Paris Agreement and Law Number 16 of 2016 mandate attainments to diminish greenhouse gas (GHG) emissions. A difference exists between the stated legal mandates and their actual execution in practice. This research aim determine PTBA’s legal responsibilities in climate change mitigation and adaptation based on international agreements and national regulations. The research employs a normative juridical method with a descriptive analytical approach. Secondary data were collected through literature studies on international agreements, laws and regulations, PTBA’s sustainability reports, and related literature. The results show that PTBA has a legal obligation supporting to climate change in reduction and adaptation. PTBA has made various efforts, such as reducing GHG emissions, reporting on environmental performance, and implementing Corporate Social Responsibility (CSR) programs. However, there are several hindering factors, such as limitations in resources and technology. The effectiveness of legal mechanisms in ensuring PTBA’s compliance also needs to be improved. This research provides policy recommendations for PTBA, the government, and stakeholders in climate change mitigation and adaptation.